Internally Fabricated Chimera Anterolateral Thigh-Amputate Flaps for Metachronous Reconstruction - Osinga, Rik (Plast Reconstr Surg Glob Open, 2019)
The chimera flap is a versatile and exciting tissue composition for the reconstruction of complex tissue defects. METHODS: Here, we present 2 cases of internally fabricated anterolateral thigh (ALT)-amputate chimera flaps for metachronous transfer. RESULTS: A 22-year-old man (case 1) developed extended soft tissue necrosis in both legs following meningococcal septicemia. Before unilateral amputation, a fasciocutaneous flap based on the posterior tibial artery perforators was saved and ectopically implanted onto the ipsilateral thigh, creating an ALT-amputate chimera flap. Three months later, it was shown that the islanded ALT-amputate chimera flap remained well vascularized on either pedicle alone. Thus, a “true chimera circulation” over the scar between the 2 flaps must have developed. Subsequent free tissue transfer to the remaining right lower leg was performed successfully with uneventful healing. A 57-year-old fisherman (case 2) suffered a traumatic avulsion of his left thumb, which was ectopically replanted onto the contralateral thigh, creating an ALT-amputate chimera flap. After 3 months, the flap was raised and orthotopically replanted successfully with arthrodesis through the metacarpophalangeal joint. The previously coapted radial digital lateral femoral cutaneous nerve was coapted in the palm, and an flexor digitorum superficialis (FDS) ring transfer was performed for flexor pollicis longus (FPL) reconstruction. CONCLUSIONS: To the best of our knowledge, these are the first case reports using the descending branch of the lateral circumflex femoral artery system for (1) temporary ectopic implantation of a thumb and (2) temporary implantation of fasciocutaneous tissue based on posterior tibial artery perforators just before below knee amputation to reconstruct the contralateral leg.